Job Pickford Family 1901 - Gorry, Joan:::::::::
Rollin's great uncle, Job Pickford, 31,with his wife, May Sullivan Pickford, 31, and daughter, Olive May Pickford, age 4 1/2. Olive May died the same year of causes unknown.